2015
DOI: 10.1155/2015/582048
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium butyricumCombined withBifidobacterium infantisProbiotic Mixture Restores Fecal Microbiota and Attenuates Systemic Inflammation in Mice with Antibiotic-Associated Diarrhea

Abstract: Antibiotic-associated diarrhea (AAD) is one of the most common complications of most types of antibiotics. Our aim was to determine the efficacy of Clostridium butyricum, Bifidobacterium infantis, and their mixture for AAD treatment in mice. AAD models were administered with single probiotic strain and probiotic mixture for short term and long term to evaluate the changes of the composition and diversity of intestinal microbiota, histopathology of the colon, and the systemic inflammation. Our data indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…Saccharomyces boulardii (S. boulardii) is an aerobic yeast [23], and early intervention with S. boulardii can alleviate porcine neonatal diarrhea [24,25]. Clostridium butyricum (C. butyricum) is a probiotic and has been used for the clinical treatment of premature infants with diarrhea by promoting the maturation of the immune function [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces boulardii (S. boulardii) is an aerobic yeast [23], and early intervention with S. boulardii can alleviate porcine neonatal diarrhea [24,25]. Clostridium butyricum (C. butyricum) is a probiotic and has been used for the clinical treatment of premature infants with diarrhea by promoting the maturation of the immune function [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…However, this protective effect was observed in a specific strain (CCM7952) and not in others, suggesting the different genetic make up and specific bacteria‐host interactions even between different strains are important to confer protection 77 . Another animal study showed that the combined effects of Clostridium butyricum and Bifidobacterium infantis protected against colitis, by restoring the gut microbiota 78 . Lactobacillus casei can also modulate the microbiota and protect against colitis, but it requires the dairy delivery matrix of milk for this effect 79 .…”
Section: The Local Effects Of Gut Microbiota On Ibdmentioning
confidence: 98%
“…77 Another animal study showed that the combined effects of Clostridium butyricum and Bifidobacterium infantis protected against colitis, by restoring the gut microbiota. 78 Lactobacillus casei can also modulate the microbiota and protect against colitis, but it requires the dairy delivery matrix of milk for this effect. 79 F. prausnitzii and the extracellular polymeric matrix isolated from its biofilm both had anti-inflammatory effects through TLR-2 signalling and modulation of IL-10 and IL-12, ameliorating DSS-induced colitis.…”
Section: The Local Effects Of Gut Microbiota On Ibdmentioning
confidence: 99%
“…This could yield true insights into the real relationships among gut microbiota, brain development and behavior. In addition, long-term high-dose antibiotic administration might impair the gut mucosal barrier and disturb normal gut homeostasis, resulting in a decline in body weight, diarrhea and anxiety-like behavior (Bercik et al, 2011;Ling et al, 2015). However, potential changes in the gut mucosa and behavior were not evaluated.…”
Section: Letter To the Editormentioning
confidence: 99%